Analisis Makna Teks Fabel Karya Jean de La Fontaine “la Cigale et la Fourm, le Coq et le Renard, le Lion devenu vieux” - Dede Kharisma Dewi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Fables are literary works in the form of literary texts in the form of exposure to stories and poems with animal characters. This study aims to determine the meaning and meaning of the Fable text of Jean de la Fontaine's three literary works, "la Cigale et la Fourmi, le Coq et le Renard, and le Lion devenu vieux". With a semantic approach and the research method used in this research is a qualitative descriptive research method, which analyzes the meaning and meaning of the sentences in the fable.